Analyzing Financial Distress: The Impact of Intellectual Capital, Operating Capacity, Capital Structure, and Operating Cash Flow with Profitability as a Mediator - Susanto, Veronica Nessie; Umiaty Hamzani; Rudy Kurniawan (Universitas Sains dan Teknologi Komputer, 2025)
Financial distress refers to a company’s persistent inability to meet financial obligations, signaling severe monetary strain that precedes formal bankruptcy or liquidation proceedings. This study investigates the impact of intellectual capital (VAICTM), operational capacity (TATO), capital structure (DER), and operating cash flow (OCF) on financial distress (Altman Z-Score), with profitability (ROA) serving as a mediating variable. The theoretical framework of this research is grounded in signaling theory, agency theory, and resource-based view theory. The study focuses on basic materials companies listed on the Indonesia Stock Exchange (IDX) between 2019 and 2023. The study utilized criterion-based sampling to select qualified respondents. Secondary datasets were analyzed through panel regression and path analysis, with Eviews 12 as the computational tool. Key findings include: (1) intellectual capital and operating capacity demonstrate a statistically significant positive influence on profitability; (2) capital structure exerts a significant adverse impact on profitability; (3) operating cash flow exhibits no statistically discernible impact on profitability; (4) both operating cash flow and profitability are positively and significantly associated with increased financial distress; (5) capital structure displays a significant inverse relationship with financial distress severity; (6) intellectual capital and operating capacity show no statistically significant associations with direct financial distress prediction; (7) profitability partially mediates the influence of intellectual capital, operating capacity, and capital structure on financial distress; and (8) profitability does not serve as a mediating variable between operating cash flow and financial distress.